Localization of Ca2+-Activated K+ Channel, SK3, in Fibroblast-Like Cells Forming Gap Junctions With Smooth Muscle Cells in the Mouse Small Intestine - Akikazu Fujita; Tadayoshi Takeuchi; Hanai Jun; Fumiaki Hata (Elsevier, 2003)
In the present study, we examined the expression and the localization of apamin-sensitive small conductance Ca2+-activated K+ channels (SK channels) in the mouse intestine. SK3-immunoreactivity (IR) was detected in both ileum and colon. Double staining experiments showed that SK3-IR was colocalized with prolyl 4-hydroxylase (PH(α))-IR, but not with c-Kit-IR which are markers of fibroblast cells and the interstitial cells of Cajal (ICC), respectively. Although SK3-IR was colocalized with vimentin-IR, which is another marker of ICC, the reactivity of SK3-immunopositive cells was weaker than that of ICC. The SK3-immunopositive cells were similarly present in the intestine of c-Kit mutant mice (W/WV), in which ICC were absent, and its wild-type mice. The immuno-electron microscopic analysis indicated that SK3 was localized in the cells that had some similar morphological features to ICC, but obviously different from ICC. The SK3-immunopositive cells had gap junctions with the smooth muscle cells. The gap junctions were smaller than those between ICC and smooth muscle cells. These results indicate expression of SK3 in fibroblast-like cells, but not in ICC, and suggest participation of the cells in the intestinal motility.